Devastating diarrhoea caused by azathioprine: management difficulty in inflammatory bowel disease. Issue 5 (May 1988) - Cox, J; Daneshmend, T K; Hawkey, C J; Logan, R F; Walt, R P
Abstract : Azathioprine toxicity complicated the management of four patients with inflammatory bowel disease. All patients received the drug as adjunctive therapy to steroids when responses to the latter were poor. After a variable sensitising period the patients developed severe diarrhoea and abdominal pain and this was believed at first to be a manifestation of their underlying diseases but rechallenge with azathioprine reproduced the problem. During three episodes described emergency admission to hospital and resuscitation with intravenous fluids was required. The cases illustrate the difficulty clinicians have in recognising drug induced effects which mimic the underlying disease. When a patient suspects a reaction to azathioprine we believe any rechallenge should only be undertaken in the controlled hospital environment.